THE INFLUENCE OF DIGITAL PAYMENT TECHNOLOGY, SERVICE SPEED, AND TRANSACTION SECURITY ON ONLINE REPURCHASE DECISIONS (CASE STUDY IN CENTRAL JAVA, INDONESIA) - Prastiwi, Iin Emy; Suprihati; Supaporn Akkapin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the influence of digital payment technology, service speed, and transaction security on online repurchase decisions among consumers in Central Java. The type of research used is quantitative with a survey approach, where data is obtained by distributing questionnaires to e-commerce consumers in the Central Java region. Data analysis was carried out using multiple linear regression using a partial significance test (t-test). The results of the study indicate that the three independent variables have a positive and significant effect on online shopping decisions again. First, digital payment technology (X1) with a significance value of 0.010 < 0.05 has a significant positive effect, which means that the easier and safer the digital payment method, the higher the tendency of consumers to make repeat purchases. Second, service speed (X2) with a significance value of 0.000 < 0.05 also has a significant positive effect, indicating that fast service encourages consumer loyalty. Third, transaction security (X3) with a significance value of 0.012 < 0.05 has a significant positive effect, in which data protection and payment security increase consumer confidence to shop again. Overall, this study confirms that digital payment technology, service speed, and transaction security are important determinants in building online consumer loyalty in Central Java.